Physiological responses at maximal aerobic swimming pacing in different distance-trials - Almeida, Tiago [UNESP]; Pessoa Filho, Dalton M. [UNESP]; Espada, Mario; Reis, Joana; Simionato, Astor [UNESP]; Siqueira, Leandro [UNESP]; Sancassani, Andrei [UNESP]; Oliveira, Joao [UNESP]; Alves, Francisco (Univ Alicante, 2019)
The aim of this study was to analyse the physiological responses of swimmers while performing different swimming distances at the maximal aerobic velocity (MAV) in order to understand the swimmers physiological impact along different levels of effort. Eight well trained swimmers performed a discontinuous incremental test for maximal oxygen uptake (VO2peak) and MAV assessment. Also, 3 different sets at the MAV, a time-limit session until exhaustion (TLim-MAV) and two distance trials of 100-m (100(mav)) and 200-m (200(MAV)) long, were performed. At the MAV tests, maximal rise of VO2 (VO2rise), oxygen initial deficit (O-2lnitialDef) and VO2 kinetics (VO2K) were determined. All tests were conducted using a breath-by-breath apparatus (K4b(2), Cosmed, Italy) connected to a swimming snorkel (new-AquaTrainer (R), Cosmed, Italy) for pulmonary gas sampling and an underwater visual pacer for velocity control. VO2peak at the incremental test was significantly higher than the VO2rise of 100mAv and 200(MAV) but not from the TLim-MAV, which presented the highest VO2rise among the MAV tests. At the TLim-MAV swimmers were able to hold the intensity for 235.7 +/- 34.1s performing 306.3 +/- 46.4m. The main finding of our work is that independently of the continuous rise of the VO2 along different swimming distances at the MAV, it does not affect the VO2K response, which remained remarkably similar. The reference values of VO2rise for each swimming distance obtained in this study, as well as the similar to 236 seconds of swimmers capacity to hold the MAV, could be take into account by coaches for their daily training routines planning.
Keywords: Maximal aerobic velocity; VO2 kinetics; VO2 slow component; Swimming; Youth athletes